2016
DOI: 10.1111/1365-2435.12779
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic rates, and not hormone levels, are a likely mediator of between‐individual differences in behaviour: a meta‐analysis

Abstract: Summary Consistent individual differences in hormone levels and metabolic rates have been proposed to be potential state variables underlying consistent individual differences in behaviour (i.e. animal personality). However, it remains unclear whether either one alone or both of these potential state variables could be an underlying driver of animal personality. We address this question using meta‐analyses of published data from bird species. We hypothesized that state variables that mediate individual diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

11
106
3

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(120 citation statements)
references
References 81 publications
(214 reference statements)
11
106
3
Order By: Relevance
“…We cannot exclude that individuals with higher corticosterone levels at the beginning of the summer were selected against through lower survival rate during the heatwave period, which could have been determined with a repeating sampling all over the exposure to the heatwaves. However, this hypothesis would involve a strong selection and a high repeatability of corticosterone levels over time, which is very unlikely according to current estimates of interindividual repeatability of GC levels (Holtmann, Lagisz, & Nakagawa, ). Our results thus alternatively suggest that individual downregulated corticosterone secretion and decreased their resting metabolism and behavioural activity to limit the costs associated with warm and dry environments (see above).…”
Section: Discussionmentioning
confidence: 99%
“…We cannot exclude that individuals with higher corticosterone levels at the beginning of the summer were selected against through lower survival rate during the heatwave period, which could have been determined with a repeating sampling all over the exposure to the heatwaves. However, this hypothesis would involve a strong selection and a high repeatability of corticosterone levels over time, which is very unlikely according to current estimates of interindividual repeatability of GC levels (Holtmann, Lagisz, & Nakagawa, ). Our results thus alternatively suggest that individual downregulated corticosterone secretion and decreased their resting metabolism and behavioural activity to limit the costs associated with warm and dry environments (see above).…”
Section: Discussionmentioning
confidence: 99%
“…The hypothesized integration of risky behaviour and age‐dependent reproduction posits that within‐individual age‐related plasticity varies among behavioural types, requiring approaches that disentangle within‐ from among‐individual age effects (van de Pol & Verhulst, ). Similarly, risky behaviours differ among individuals (Bell, Hankison, & Laskowski, ; Holtmann, Lagisz, & Nakagawa, ) but simultaneously exhibit within‐individual age‐dependent plasticity (Araya‐Ajoy & Dingemanse, ; Brommer & Class, ; Class & Brommer, ; Fisher, David, Tregenza, & Rodriguez‐Munoz, ; Patrick, Charmantier, & Weimerskirch, ). Repeated measures are thus required to estimate relationships between individual‐level behaviour and reproductive senescence while avoiding bias due to within‐individual plasticity (Niemelä & Dingemanse, , ).…”
Section: Introductionmentioning
confidence: 99%
“…Research in a variety of taxa has shown that behavioural traits exhibiting personality often correlate across contexts, forming larger clusters termed behavioural syndromes (Sih, Bell, Johnson, & Ziemba, ). Understanding the structure of behavioural syndromes is crucial for quantifying their influence on evolutionary and ecological processes (Dochtermann & Dingemanse, ; Wolf & Weissing, ) and establishing the proximate mechanisms of personality upon which natural selection acts (Araya‐Ajoy & Dingemanse, ; Holtmann, Lagisz, & Nakagawa, ; Van Oers & Mueller, ).…”
Section: Introductionmentioning
confidence: 99%